Perlindungan Anak Di Luar Nikah Dalam Perspektif Hukum Islam Dan Hukum Positif - Adzimatul Khusnah; Ach Faisol; Moh Muslim (Jurnal Hikmatina, 2020)
AbstrakThe results of the study concluded that according to decision of the constitutional court No. 46/PUU-VIII/2010 which equates the legal status between a legal child and an extramarital child in connection with civil law. In Islamic law and positive law, parents both have the full obligation to care for and protect children. The safi’I school and the Hanafi school of law allow the marriage of pregnant women out of wedlock, because according to them there are no iddahs for pregnant women. According ti Imam Maliki and Imam Hambali, they both agreed that the status of the child out of wedlock was only for the mother and her mother’s family. That is because men are not allowed to marry pregnant women out of wedlock. Kata Kunci: Perlindungan Anak